miR-128a acts as a regulator in cardiac development by modulating differentiation of cardiac progenitor cell populations - Hölscher, Sarah; Stich, Theresia; Diehm, Anne; Lahm, Harald; Dreßen, Martina; Zhang, Zhong; Neb, Irina; Aherrahrou, Zouhair; Erdmann, Jeanette; Schunkert, Heribert; Santamaria, Gianluca; Cuda, Giovanni; et al. (International journal of molecular sciences, 2020)
MicroRNAs (miRs) appear to be major, yet poorly understood players in regulatory networks guiding cardiogenesis. We sought to identify miRs with unknown functions during cardiogenesis analyzing the miR-profile of multipotent Nkx2.5 enhancer cardiac progenitor cells (NkxCE-CPCs). Besides well-known candidates such as miR-1, we found about 40 miRs that were highly enriched in NkxCE-CPCs, four of which were chosen for further analysis. Knockdown in zebrafish revealed that only miR-128a affected cardiac development and function robustly. For a detailed analysis, loss-of-function and gain-of-function experiments were performed during in vitro differentiations of transgenic murine pluripotent stem cells. MiR-128a knockdown (1) increased Isl1, Sfrp5, and Hcn4 (cardiac transcription factors) but reduced Irx4 at the onset of cardiogenesis, (2) upregulated Isl1-positive CPCs, whereas NkxCE-positive CPCs were downregulated, and (3) increased the expression of the ventricular cardiomyocyte marker Myl2 accompanied by a reduced beating frequency of early cardiomyocytes. Overexpression of miR-128a (4) diminished the expression of Isl1, Sfrp5, Nkx2.5, and Mef2c, but increased Irx4, (5) enhanced NkxCE-positive CPCs, and (6) favored nodal-like cardiomyocytes (Tnnt2+, Myh6+, Shox2+) accompanied by increased beating frequencies. In summary, we demonstrated that miR-128a plays a so-far unknown role in early heart development by affecting the timing of CPC differentiation into various cardiomyocyte subtypes.
Gesehen am 18.05.2020